Shelf Stability and Optimization of Drying Time and Temperature of Guayabano (Annona muricata) Candy - Belen Inderio; Emma Ruth Bayogan; Emelyn Magkidong (Davao Research Journal)
This study was divided into three parts. Part one dealt with the determination of storability ambient conditions of unblended and blended Guayabano candy treated with alum or lime, processed using the fast and slow methods, and oven-dried at 800C. Results showed that the Guayabano candy had a maximum storability of almost 3 weeks. Termination of shelf-life was marked by the presence of molds and accumulation of moisture on product surface. Blended samples were preferred over unblended samples for aesthetic and economic reasons. The latter had nonuniform size and shape and processing incurred wastage due to trimmings. Treatments with alum and lime did not have direct effect on shelf stability. Similarly, extent of processing using the slow and fast methods and final moisture content did not affect shelf stability. The second part aimed to verify part 1 results. The kind of packaging material used in wrapping the products affected shelf stability. Water cellophane was a better moisture barrier compared to Japanese paper. The third part was a preliminary study on the optimum drying times of Guayabano candy dried at either 80 or 900C, an increase in the drying temperature from 80 to 900C did not result in the expected reduction in the number of drying hours due to case hardening. In case hardening, product surface hardened due to high temperature which' served as barrier to moisture migration towards the surface.